2011
DOI: 10.1080/10926771.2011.595762
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Levels of Severity of Childhood Trauma among Mexican Female Sex Workers: A Comparison of Two Mexico Border Cities

Abstract: The purpose of this study is to examine the prevalence of childhood trauma in a sample of female sex workers in Mexico. One hundred and nine female sex workers were recruited from Nuevo Laredo and Ciudad Juarez and administered the Childhood Trauma Questionnaire. Findings reveal a high prevalence rate of childhood trauma among the total sample (94%). Nuevo Laredo sex workers had significantly higher total mean and subscale scores and levels of severity compared to Ciudad Juarez sex workers. This research is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We found that CSA rate was considerably high in sex workers (41%), similar to that in previous studies (Dickson-Gomez et al, 2006; El-Bassel et al, 2001; Hankel et al, 2016). Sex workers in one of the included studies had their first sexual experience at an early age (Cepeda, 2011), which suggests that they may be at a higher risk of sexual abuse during their work. However, there were very few eligible studies on sex workers as well as prisoners; therefore, the rate may also have been affected by bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that CSA rate was considerably high in sex workers (41%), similar to that in previous studies (Dickson-Gomez et al, 2006; El-Bassel et al, 2001; Hankel et al, 2016). Sex workers in one of the included studies had their first sexual experience at an early age (Cepeda, 2011), which suggests that they may be at a higher risk of sexual abuse during their work. However, there were very few eligible studies on sex workers as well as prisoners; therefore, the rate may also have been affected by bias.…”
Section: Discussionmentioning
confidence: 99%
“…Some subgroups lacked adequate numbers of eligible studies, and there was existence of publication bias. Lastly, there were a few included studies that employed local language version of CTQ-SF in non-English-speaking countries; there is lack of information related to translation equivalence, conceptual equivalence, and metric equivalence of these versions across cultural groups (Cepeda, 2011; Coppens et al, 2017; Driessen et al, 2006; Martsolf, 2004; Schafer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 107 venues in Nuevo Laredo and 76 venues in Ciudad Juarez were identified. A random sample of 44 venues in Ciudad Juarez and 30 in Nuevo Laredo were selected for the recruitment of the sample of 109 sex workers (see Cepeda, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…A total of 107 venues in Nuevo Laredo and 76 venues in Ciudad Juarez were identified. A random sample of 44 venues in Ciudad Juarez and 30 in Nuevo Laredo were selected for the recruitment of the sample of 109 sex workers (see Cepeda, 2011). The inclusion criteria for participation was women above the age of 18, working in one of the selected venues, and self-reported participation in the exchange of sex for money or drugs in the respective venue.…”
Section: Methodsmentioning
confidence: 99%